Are Follicular Regulatory T Cells Involved in Autoimmune Diseases? - Gong, Yonglu; Tong, Jia; Wang, Shengjun (Frontiers in Immunology, 2017)
In the germinal center, follicular helper T (TFH) cells interact with B cells and undergo a series of germinal center (GC) reactions to ultimately produce high-affinity antibodies and memory plasma cells. Recent studies have found a subpopulation of regulatory T cells called follicular regulatory T (TFR) cells. TFR cells can inhibit TFH cells and/or B cells in a variety of ways to specifically regulate GC reactions. Dysfunction of TFR cells may lead to immune disorders and a variety of autoimmune diseases. In this review, we summarize the differentiation and function of TFR cells and provide an overview of TFR cells in autoimmune diseases.